Law and Legal Politics: The case for the formation of Law Number 12 of 2010 concerning the Scout Movement - Sahlim, Muhamad (Definisi: Jurnal Agama dan Sosial Humaniora, 2023)
The Scout Movement is a place for coaching its members in building character. In other words, the Scout Movement is a scouting organization that is used to carry out scouting practices. As an educational organization, of course, the Scout Movement has a pattern and mechanism for coaching students according to class or age. The Scout Movement Act is a form of revitalization of the Scout Movement which is aligned with the times. And make the highest legal umbrella in every activity base that will be carried out. The result of his research on the Scout Movement Law is to find out how far the process of formation has gone to its implementation in the field, bearing in mind that the Scout Movement Law is flexible and can be adapted to changing times. This research on the Scout Movement Act is aimed at finding out how strong its position is in every implementation of activities organized by the Scout Movement. As well as the benefits of the activities carried out, for the people in the surrounding environment so that they remain within the corridor of the Scout Movement’s code of ethics, namely Tri Satya and Dasa Dharma.